Tarian dan Topeng Hudoq Kalimantan Timur: suatu Kajian Filsafat Seni - Fauzia Latif (Bina Nusantara University, 2013)
Indonesia is a rich country of arts and cultures. Dayak culture is one example. Dayak community has distinctive and unique of culture, from art, social system, to belief system. Hudoq mask and dance are samples of the culture of East Kalimantan Dayak community which are not decorative shapes and motifs only, but also full of philosophical meaning and symbol of the community’s faith. The results of this study are very important to record the progress of Dayak culture from ancient to present time, as well as to preserve the high values of Dayak community, as Indonesian people. This study can be used as materials in further Indonesian culture studying and served as examples to the upcoming art design world.